Screening for potential antidiabetes and antioxidant activities of selected plants from East Kalimantan, Indonesia - RICO RAMADHAN; ALFINDA NOVI KRISTANTI; RUDIANTO AMIRTA; IRAWAN WIJAYA KUSUMA; PREECHA PHUWAPRAISIRISAN; MUHAMMAD TAUFIQ HAQIQI; SAPARWADI SAPARWADI (Society for Indonesian Biodiversity, 2019)
Abstract. Ramadhan R, Kristanti AN, Amirta R, Kusuma IW, Phuwapraisirisan P, Haqiqi MT, Saparwadi. 2019. Screening for potential antidiabetes and antioxidant activities of selected plants from East Kalimantan, Indonesia. Biodiversitas 20: 1820-1826. Ten selected plants in this study have been used traditionally in West Kutai, East Kalimantan as medicinal plants. This study aimed to screen and evaluate the in vitro antidiabetic and antioxidant activity of methanol extracts of selected plants from East Kalimantan. The antidiabetic activity was carried out by ?-glucosidase inhibitory activity with maltose and sucrose as substrates while antioxidant activity was determined by free radicals scavenging activity against DPPH, ABTS and Nitric Oxide (NO). The results showed that Garcinia riedeliana extract had strong inhibitory activity with an IC50 value of 0.04 mg/mL followed by  Shorea laevis, Pternandra azurea and Bridelia tomentosa with IC50 values of 0.12; 0.15 and 0.16 mg/mL in maltose respectively, while quercetin as positive control had an IC50 value of 0.08 mg/mL. G.riedeliana extract also showed good ?-glucosidase inhibitory activity with an IC50 value of 0.23 mg/mL in sucrose as substrate. The results on antioxidant activity showed that all extracts have IC50 value against free radicals DPPH, ABTS, and nitric oxide. The most active extract as ?-glucosidase inhibitory activity and antioxidant activity was G. riedeliana extract. These findings provide the scientific evidence that one species of medicinal plants from East Kalimantan might be potential as an antioxidant and ?-glucosidase inhibitor.